Kampanye Pengembalian Bahan Organik Tanah Untuk Mengatasi Permasalahan Hama Penyakit Tanaman Durian Di Kecamatan Doro Kabupaten Pekalongan - Bonjok Istiaji; Abdul Munif; Ahmad Yuda Pratama; Rifka Lailatul Hikmah (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Pertanian Bogor, 2019)
Soil nutrient imbalance comparing roughly the amount of fertilizer added and harvest taken implies on pest and disease problems of durian (Durio zibethinus) at district of Doro, Pekalongan regency. The aims of activity are campaigning the importance of soil organic matter returning and working together with local farmers for healthier plant husbandry. The activity started with a survey process and the taking of several trees as samples to carry out plant sanitation activities with local partner farmers. This activity is carried out to fulfill plant nutrition and nutrients by returning soil organic matter used as compost. Bio-Hara Plus liquid organic fertilizer and pesticide formulations were introduced to farmers as activators to accelerate the decay of organic material or composting. Socialization was also carried out to farmers about plant health programs and direct practices to several partner farmers This method is introduced to partner farmers and is expected to become a model for other farmers. Bio-Hara Plus was responded by both farmers and local communities and the potential for collaboration with Village-Owned Enterprises regarding the supply of Bio-Hara plus and other plant health products.